Quality Of Elderly Life With Chronic Diseases In The Working Area of Kembangan District Hospital - Maringka, M C Gina; W.Rahardjo, Tri Budi; Suratmi, Tri (Jurnal Indonesia Sosial Sains, 2023)
The success of health development in Indonesia has increased the life expectancy of the Indonesian people. West Jakarta Kembangan Hospital has responsibility for improving the quality of life of the elderly in their working area, in line with Government Policy Number 17 of 2014 concerning Geriatric Service Standards in Hospitals. The aim of the study was to analyze the quality of life of elderly people with chronic diseases in the working area of Kembangan Hospital, West Jakarta in 2023. This study used a quantitative approach with a cross-sectional design, with an elderly population in the working area of Kembangan Hospital and a sample size of 60 elderly people by Simple Random Sampling. The research instrument used the WHOQOL-Bref questionnaire, while the questionnaire was used to measure the variable characteristics of the elderly. Research time: Juni 2023. Data analysis techniques using univariate, bivariate and multivariate analysis. The results showed that the most chronic diseases were hypertension (50%), diabetes mellitus (23.7%), hypertension and diabetes mellitus (6.7%), hypertension and heart (6.7%), arthritis (3.3%), the rest is a combination of existing chronic diseases. The proportion of high quality of life for the elderly (63.3%) and low quality of life for the elderly (36.7%), marital status, education, employment, income and status of residence as well as the length of chronic disease in the elderly are related to the quality of life for the elderly, while age, gender, name of chronic disease and the number of chronic diseases are not related to the quality of life of the elderly. The dominant variable related to the quality of life of the elderly is income with OR = 0.269. Suggestions that can be recommended to the Kembangan Hospital are reactivating geriatric services through promotive efforts for elderly health so that chronic diseases in the elderly can be detected early and receive optimal treatment so as to improve the quality of life of the elderly, can open geriatric innovation services that are "One Stop Service for the Elderly"